Literature Exposure and Vocabulary Acquisition on English Language Learning among Bachelor of Secondary Education - Mon, Anthony M.; Almo, Ellhayzza Nicole B.; Estella, Maria Jezyl T.; Dizon, Joseph Deo D.; Menes, Maricar B.; Limon, Aaron M.; Mundia, Samantha (Future Science / FSH-PH Publications, 2025)
This study explored the challenges faced by Bachelor of Sec-ondary Education (BSEd) Major in English students at President Ramon Magsaysay State University (PRMSU) Santa Cruz Campus during the Academic year 2023-2024 in learning English Lan-guage through literature exposure, frequent reading of literature materials, and vocabulary acquisition. The research was guided by Krashen's Implicit Vocabulary Learning Theory and Ru-melhart's Schema Theory. A quantitative research design utiliz-ing a survey questionnaire via Google Forms was conducted with 60 BSEd English students at PRMSU Santa Cruz to assess de-mographics, literature exposure frequency, and challenges in vocabulary acquisition and literature exposure.The results indicated that although literature exposure was perceived as beneficial for vocabulary development, students encountered challenges such as difficulties in teaching methods, time constraints, understanding complex texts, limited exposure to the target language, and technological unfamiliarity. Addition-ally, female students faced challenges in all macro language skills areas. Notably, the students' year level did not significantly influ-ence the challenges they encountered. However, a difference was observed between sex in challenges related to language exposure and reading comprehension. Furthermore, a positive correlation was found between challenges in vocabulary acquisition, macro language skills, vocabulary instruction, and vocabulary develop-ment.In conclusion, the study highlights the significant impact of challenges in learning English through literature exposure, fre-quent reading, and vocabulary acquisition on BSEd-English students. The researchers recommend adopting a comprehen-sive approach to address these challenges effectively.